Association of metals with the risk and clinical characteristics of Parkinson's disease. (October 2018) - Kim, Mi-Jung; Oh, Shin-Bi; Kim, Juyeon; Kim, Kiju; Ryu, Ho-Sung; Kim, Min Sun; Ayton, Scott; Bush, Ashley I.; Lee, Joo-Yong; Chung, Sun Ju
Abstract: Introduction: While metals have been implicated in the pathophysiology of Parkinson's disease (PD), the clinical evidence is scarce. Further, the contribution of metals for the risk or clinical presentation of PD remains to be explored. Methods: To investigate the associations between the level of metals in blood serum and PD risk or clinical presentation, including sex-related differences, we studied 325 PD patients and age- and sex-matched 304 controls. We collected clinical data of the PD patients, including age at onset, PD duration, levodopa-equivalent dose (LED), Hoehn and Yahr stage (H-Y stage), presence of motor fluctuation, levodopa-induced dyskinesia (LID), freezing of gait, hallucination, and Mini-Mental State Examination (MMSE) score. Iron, copper, and zinc levels in serum were assayed by inductively coupled plasma mass spectrometry. Statistical analyses were performed to determine the sex-related differences in metal levels. Results: Among the three metal elements tested, serum copper levels showed significant correlations with PD risk or clinical presentation. Higher copper levels were associated with a decreased PD risk. Higher copper or lower iron levels were associated with the risk of LID in women. Serum copper levels were negatively correlated with MMSE scores in PD patients. Conclusions: This clinical study suggests significant associations between serum metal levels and PD risk or essential clinical features, demonstrating the possible roles of metals in PD pathogenesis or symptom development. Highlights: Clinical evidence on the implication of metal in Parkinson's disease (PD) is rare. Higher copper level in serum is associated with a decreased PD risk. Higher copper or lower iron is associated with levodopa-induced dyskinesia in women. Serum copper level is negatively correlated with MMSE scores in PD patients. There are associations between serum metals and PD risk or clinical presentation.